Occupational Safety and Health Analysis with JSA Method and HAZOP - Aulia, Rangga (Jurnal Teknologi, 2025)
Aulia Karya workshop is a small and medium business which is a company engaged in the manufacturing industry, and in the workplace there is a very large potential hazard, namely shortness of breath due to inhalation of welding fumes, and explosions of nitrogen and oxygen gases. The purpose of this study is to analyze potential hazards using the Job Safety Analysis (JSA) method and to identify the causes of operational disturbances using the Hazard and Operability Study (HAZOP) method at Aulia Karya workshop. using Job Safety Analysis (JSA) and Hazard and Operability Study (HAZOP) methods. data that used is work accident data. Based on data processing carried out the value of the frequency of work accidents (frequency rate) in the 12 months of 2020/2021 namely the number of work accidents of 0.002 per thousand working hours.